2013
DOI: 10.1007/s10163-013-0223-9
|View full text |Cite
|
Sign up to set email alerts
|

Total lead content and its bioaccessibility in base materials of low-cost plastic toys bought on the Beijing market

Abstract: The neurological hazards of lead are wellknown. Few studies have focused on lead content in plastic toys, especially in China. Therefore, this study aimed to determine total lead content in low-cost plastic toys bought in Beijing, based on the bioaccessibility (BA) of lead through an in vitro leaching method. A total of 27 of the 72 items (37.5 %) examined exceeded the American toy safety limit (100 mg/kg), but HCl extraction results showed that all the samples met the Chinese standard (\90 mg/kg). The BA of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…During the selection, samples with lower price were preferred. This was because previous studies reported that cheaper toys and jewelry may contain higher metal levels mainly due to the recycling of contaminated materials or the lack of regulation for raw materials (Kang and Zhu, 2013;Weidenhamer and Clement, 2007a,b). The products were grouped into five categories: 13 metallic toys and jewelry (MTJ), 19 plastic toys, 3 paper/wood toys, 8 brittle/pliable toys, and 2 paint coating from toys.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…During the selection, samples with lower price were preferred. This was because previous studies reported that cheaper toys and jewelry may contain higher metal levels mainly due to the recycling of contaminated materials or the lack of regulation for raw materials (Kang and Zhu, 2013;Weidenhamer and Clement, 2007a,b). The products were grouped into five categories: 13 metallic toys and jewelry (MTJ), 19 plastic toys, 3 paper/wood toys, 8 brittle/pliable toys, and 2 paint coating from toys.…”
Section: Methodsmentioning
confidence: 97%
“…Only PL8 (toy plane) contained elevated Pb (44 mg kg À1 ) in the current study, which was much lower than those in previous results. For example, Kang and Zhu (2013) reported that 27 of 72 plastic toys from Beijing market contain >100 mg kg À1 Pb. The low Pb contents in metallic toys and jewelry and plastic toys in our results suggested that recent Pb regulations have positive effect on the safety of children's products.…”
Section: Metal Concentrations In 13 Metallic Toys and Jewelrymentioning
confidence: 98%
“…Twenty-five cheap toy samples imported from China were purchased from different markets in Lagos State, Nigeria. Cheap toys were sampled because it has been reported that cheaper toys may contain higher metal concentrations of PTMs [2,21]. The samples were taken to the laboratory, thoroughly washed, and evaluated with the Beilstein indicative test for halogens [22] to determine the presence of PVC.…”
Section: Sample Collection and Preparationmentioning
confidence: 99%
“…Results of the study found that over 50 toys contained Pb concentrations exceeding those allowed by Brazilian law, which stipulates a limit of 600 ppm for lead (Silva et al 2018;Brazil 2008). Similarly, the presence of these and other toxic metals in plastic toys has been reported in many countries, including Kazakhstan (Akimzhanova et al 2020), China (Kang and Zhu 2015;Cui et al 2015) and the UK (Turner 2018).…”
Section: Introductionmentioning
confidence: 61%